2010
DOI: 10.1515/hf.2010.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of black liquors from kraft pulping of first-thinning Scots pine (Pinus sylvestris L.)

Abstract: Formation of hydroxy acids and soluble lignin fragments was investigated during conventional kraft pulping of first-thinning Scots pine (Pinus sylvestris L.) stem wood and its long-fiber outer part and short-fiber inner part. The results indicate that there are characteristic differences in the formation of hydroxy acids in these specific tissues, due to the slightly different contents of cellulose, hemicelluloses, and lignin. Notable are the differences in the formation of xylan-derived acids (2-hydroxybutano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Quantitative preparation A lignin sample from 3 mL of black liquor from aspen kraft pulping was prepared by acid precipitation according to a previous report (Rautiainen and Alén 2010). The lignin precipitate was washed by 5 mM H2SO4 twice and then with water for three times, respectively.…”
Section: Assay Of Lignin In Black Liquormentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative preparation A lignin sample from 3 mL of black liquor from aspen kraft pulping was prepared by acid precipitation according to a previous report (Rautiainen and Alén 2010). The lignin precipitate was washed by 5 mM H2SO4 twice and then with water for three times, respectively.…”
Section: Assay Of Lignin In Black Liquormentioning
confidence: 99%
“…Lignin concentration in black liquor was determined using the absorbance at 280 nm according to the method of Rautiainen and Alén (2010).…”
Section: Uv Spectroscopymentioning
confidence: 99%
“…Spent liquor from the kraft pulping process also contains components that can contribute significantly to cationic demand (Alber et al 1998;Bikova et al 2000;Vu et al 2003;Lisboa et al 2005;Neto et al 1999;Sjöholm et al 2000;Rautiainen and Alén 2010;Jansson and Brännvall 2011;Magaton et al 2011). Even though kraft pulping systems invariably employ devices called brown-stock washers to remove black liquor from the pulp before it arrives at the paper machine system, the washing process is never 100% complete (Hart 2011;Pacheco et al 2006).…”
Section: Black Liquor Carry-overmentioning
confidence: 99%
“…In the case of kraft pulps, though lignin is clearly released from the fiber (Alber et al 1998;Bikova et al 2000;Duarte et al 2003;Rautiainen and Alén 2010), the relationship of such lignin to cationic demand is not well known. Alber et al 1998 found that a totally chlorine free (TCF) bleaching cycle was particularly prone to releasing a lot of lignin into the water phase.…”
Section: Lignin-related Contributors To Cationic Demandmentioning
confidence: 99%
See 1 more Smart Citation